Badminton shuttlecock aerodynamics: synthesizing experiment and theory - Chan, C. M.; Rossmann, J. S. (Sports Engineering, 2012)
In this study, the flight performance of four models of shuttlecocks, two with feather skirts and two with plastic, is investigated. The aerodynamic forces of each shuttlecock at varying air speed and angle of attack are measured in a subsonic wind tunnel. Empirical correlations derived from these data are then incorporated into an adaptive, shuttlecock-specific numerical trajectory simulation. These simulated trajectories are in good agreement with experimental results, with average and maximum errors of 2.5 and 9.1% in vertical distance travelled. The aerodynamically adaptive trajectory model is used to analyse four common types of badminton shot: serve, net, smash and high clear. From these simulations, it is found that the trajectory paths of the higher quality plastic shuttlecock most closely mimic those of the feather shuttlecock of same speed grade. Results of both aerodynamic testing and trajectory simulation provide quantitative support for players` preference for the `feel` and responsiveness of feather shuttlecocks. It is also observed that plastic shuttlecocks fly faster than do feather shuttlecocks under smash shots, a behaviour explained by a reduction of drag due to skirt deformation observed in wind tunnel experiments at high flight velocity. The results of the study highlight the influence of shuttlecock design and material on shuttlecock flight.